2009
DOI: 10.1080/10253890802372414
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum cortisol, cardiovascular function and neurological outcome following acute global hypoxia in the newborn piglet

Abstract: Perinatal asphyxia is a significant contributor to neonatal brain injury. However, there is significant variability in neurological outcome in neonates after global hypoxia-ischemia. The aims of this study were to identify which physiological response/s during global hypoxia-ischemia influence the severity of brain injury and to assess their relative importance. Hypoxia/hypercapnia was induced in 20 anaesthetized piglets by reducing the inspired oxygen fraction to 10% and the ventilation rate from 30 to 10 bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 38 publications
0
19
0
2
Order By: Relevance
“…Perinatal asphyxia can be considered as an extreme of a stress situation. In a study on the stress response to hypoxia in neonatal piglets, maintenance of cardiovascular function and a higher serum cortisol concentration were associated with a better neurological outcome [27]. Further studies are needed to determine whether copeptin is related to asphyxia severity and whether copeptin may improve outcome prognostication after asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal asphyxia can be considered as an extreme of a stress situation. In a study on the stress response to hypoxia in neonatal piglets, maintenance of cardiovascular function and a higher serum cortisol concentration were associated with a better neurological outcome [27]. Further studies are needed to determine whether copeptin is related to asphyxia severity and whether copeptin may improve outcome prognostication after asphyxia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Harris et al (2008) showed that piglet capacity to tolerate asphyxia depends on each individual, since there is a large variation in the cardiovascular response and cortisol concentrations allowing them to survive birth asphyxia. The incidence and the degree of birth asphyxia experienced in newborn piglets during birth are highly variable and rather unpredictable.…”
Section: Vitality: Umbilical Cord and Asphyxiamentioning
confidence: 99%
“…This result suggests that the piglets regulate with a higher initial variance, but then already regulate to lower variability in terms of adapting to the oxygen deficit. Harris et al [34] investigated the associations between cardiovascular function and neurological outcome following acute global hypoxia in 20 anaesthetized newborn piglets and found a high degree of variability in cardiovascular function (mean arterial blood pressure and HR) in response to hypoxia. In addition, our study revealed that increased HRV diminished during prolonged hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CCE , the blood pressure time series revealed a highly significant synchronisation index SYS_DIA_SI for HYP1 and HYP2, suggesting a high predictability level for DIA when SYS is given. The potential reason for the higher blood pressure synchronisation could be the augmented peripheral vasoconstriction, due to increased sympathetic activity during normocapnic hypoxia [34]. After initialising recovery, the synchronisation index decreased in the direction of normoxic values.…”
Section: Discussionmentioning
confidence: 99%